2017
DOI: 10.1002/2017jb014037
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the causal relationship between slow slip and tectonic tremor in Guerrero, Mexico

Abstract: Similar to other subduction zones, tectonic tremors (TTs) and slow‐slip events (SSEs) take place in the deep segment of the plate interface in Guerrero, Mexico. However, their spatial correlation in this region is not as clear as the episodic tremor and slip observed in Cascadia and Japan. In this study we provide insights into the causal relationship between TTs and SSEs in Guerrero by analyzing the evolution of the deformation fields induced by the long‐term 2006 SSE together with new locations of TTs and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…Considering the significant differences in slow earthquake behavior along the subduction zone (e.g., near constant activity in some areas, variations in SSE magnitudes and tremor zone width, and the presence of short‐ and long‐term SSEs) the Mexican subduction zone presents variations that are more similar to the Nankai subduction zone than the more homogeneous behavior seen in Cascadia. In addition, large long‐term SSEs occur updip from tremors area, while short‐term SSEs occur downdip in the sweet spot (Villafuerte & Cruz‐Atienza, ), similar to that observed in Nankai (Obara & Kato, ). However, the tremor area width varies significantly along the Mexican subduction zone interface.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Considering the significant differences in slow earthquake behavior along the subduction zone (e.g., near constant activity in some areas, variations in SSE magnitudes and tremor zone width, and the presence of short‐ and long‐term SSEs) the Mexican subduction zone presents variations that are more similar to the Nankai subduction zone than the more homogeneous behavior seen in Cascadia. In addition, large long‐term SSEs occur updip from tremors area, while short‐term SSEs occur downdip in the sweet spot (Villafuerte & Cruz‐Atienza, ), similar to that observed in Nankai (Obara & Kato, ). However, the tremor area width varies significantly along the Mexican subduction zone interface.…”
Section: Discussionsupporting
confidence: 66%
“…These events occur every 4 years and last nearly a year (Figure ). In addition, Frank et al () used summations of GPS time series aligned at the moments of LFE bursts and detected short‐term SSEs downdip of the slip area of the larger long‐term events, which have been recently shown to take place in the sweet spot (Villafuerte & Cruz‐Atienza, ). These short‐term SSEs have a maximum magnitude of 6.4 and a recurrence period of about 90 days.…”
Section: Slow Slip Eventsmentioning
confidence: 99%
“…Other authors have demonstrated that tremor and LFE activity is a precise indicator of slow fault slip from SSEs (e.g., Frank et al, , ; Frank, Shapiro, Husker, Kostoglodov, & Campillo, ; Hawthorne & Rubin, ; Villafuerte & Cruz‐Atienza, ). Here we observe this same relationship for tremor activity in Mexico during large SSEs, as summarized in Table .…”
Section: Discussionmentioning
confidence: 99%
“…Tectonic tremor, low-frequency, and very lowfrequency earthquakes have also been observed in Guerrero close to the plate interface at 40-to 45-km depth during the occurrence of SSEs (Payero et al, 2008;Kostoglodov et al, 2010;Husker et al, 2012;Frank et al, 2014;Cruz-Atienza et al, 2015;Maury et al, 2016;V. M. Cruz-Atienza et al, unpublished manuscript, 2018, see Data and Resources), suggesting that such phenomena are causally related (Villafuerte and Cruz-Atienza, 2017) as postulated for other subduction zones (e.g., Hirose and Obara, 2010;Bartlow et al, 2011). ▴ Figure 1.…”
Section: Introductionmentioning
confidence: 83%